2023
DOI: 10.1111/gcb.16917
|View full text |Cite|
|
Sign up to set email alerts
|

Cover crops do not increase soil organic carbon stocks as much as has been claimed: What is the way forward?

Vincent Chaplot,
Pete Smith

Abstract: When compared to virgin land (forest and grassland), croplands store significantly lower amounts of organic carbon (OC), mainly as a result of soil tillage, and decreased plant inputs to the soil over the whole year. Doubts have been expressed over how much reduced and zero tillage agriculture can increase OC in soils when the whole soil profile is considered. Consequently, cover‐crops that are grown in‐between crops instead of leaving soils bare appear as the “last man standing” in our quest to enhance cropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Our aim is not to discourage the practice of using CC in arable agriculture, which, as indicated in Chaplot and Smith (2023b), can have multiple benefits. Rather, it is to demonstrate potential pitfalls in meta-analyses, if they include studies that do not meet quality criteria.…”
Section: Many Tens To Hundreds Of Experiments Have Been Performedmentioning
confidence: 99%
See 2 more Smart Citations
“…Our aim is not to discourage the practice of using CC in arable agriculture, which, as indicated in Chaplot and Smith (2023b), can have multiple benefits. Rather, it is to demonstrate potential pitfalls in meta-analyses, if they include studies that do not meet quality criteria.…”
Section: Many Tens To Hundreds Of Experiments Have Been Performedmentioning
confidence: 99%
“…Poeplau et al. (2023) have raised concerns regarding our recent contribution to Global Change Biology (Chaplot & Smith, 2023b) and conclude that cover crops (CC) do increase soil organic carbon stocks (SOCS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the paper by Chaplot and Smith (2023), we incorrectly reported that the study by Thomsen and Christensen (2004) reported on soil bulk density (BD). Our central conclusion, that current studies do not provide sufficient reliable data to conclude an impact of cover crops on soil organic carbon stocks, and our suggestions for future experiments remain unchanged.…”
Section: Authors <1 M No Esm <3 Years No Bd No Control Cash Crop N ≤ ...mentioning
confidence: 99%
“…Beillouin et al (2023) performed a second-order global meta-analysis and identified five cover crop meta-analyses, showing a significant positive mean effect of cover crops on SOC (+11.6%). Obviously, international standards to carry out systematic reviews and meta-analyses (Gurevitch et al, 2018) were not followed by Chaplot and Smith (2023), which is a major shortcoming of this paper.…”
mentioning
confidence: 99%